World Bank Corporate Scorecard April 2013 : Integrated Results and Performance Framework - World Bank (Washington, DC, 2013)
The corporate scorecard provides information on the Bank's overall performance and the results achieved by its clients, against the backdrop of progress on global development objectives. The corporate scorecard facilitates strategic dialogue between management and the Board on progress made and areas that need attention. The corporate scorecard uses an integrated results and performance framework, which is organized in a four-tier structure that groups indicators along the results chain. Tier one indicators show the long-term development outcomes that countries are achieving, and provide the context and direction for the Bank's work. These high-level outcomes cannot be attributed directly to the Bank, because countries and their development partners all contribute to these achievements over the long term through a combination of multi-sector interventions, actions, and policy decisions. These indicators are also affected by external factors such as global crises. Tier two highlights development results that countries have achieved with Bank support. Tier three indicators provide information on the effectiveness of the Bank s operations and services. Tier four focuses on organizational effectiveness and modernization, and assesses how well the Bank is functioning and adapting to better support countries in achieving results.